Development and validation of slagging model for typical coals in drop-tube furnace. (1st April 2021) - Pei, Jianjun; Chen, Zhen; Wang, Haiming; You, Changfu
Highlights: The slagging weight of typical coals were measured online in drop-tube furnace. Particle-sticking probability was calculated by online measuring results. The particle temperature is the main factor of slagging. Particle-sticking-probability model was built via the particle temperature and composition. Abstract: Slagging occurs frequently in boilers owing to the usage of low-NOx combustion technologies. Slagging reduces the heat transfer from the water wall and severely affects the operational safety of boilers, especially when low-rank coals, such as those with a high ash content, low calorific value, or low ash melting point, are burnt. In this study, slagging was measured online in a drop-tube furnace, and the variation in the ash slagging rate with the furnace temperature was determined for different types of coals. The particle-sticking probability was calculated based on the ratio of the slagging rate and particle-impacting probability. A particle-sticking-probability model that considers only the chemical composition and temperature of the coal particles was developed. This model was then verified through a comparison of its predictions with the experimental data. The proposed model does not need to consider the critical viscosity and velocity of the particle. Thus, the slag deposition values calculated using this model were found to be the closest to the experimental results. Furthermore, using this new model for the numerical simulation of a 600 MWe tangential-fired utility boiler, it was found that with an increase in the boiler load, the slagging on the water wall became considerably severer, especially on the back wall. Overall, this model could accurately predict the slagging on the water wall in the actual boiler.